218k views
2 votes
Question attached as screenshot below: I am following along diligently, please help me.

Question attached as screenshot below: I am following along diligently, please help-example-1
User ULLAS K
by
5.2k points

1 Answer

5 votes

To solve this problem, we have to use implicit derivation. To do it, derive each expression as usual and multiply by y' each expression that contains y, this way:


\begin{gathered} 4+xy=y^2 \\ y+xy^(\prime)=2yy^(\prime) \end{gathered}

Now, solve the obtained equation for y':


\begin{gathered} xy^(\prime)-2yy^(\prime)=-y \\ y^(\prime)(x-2y)=-y \\ y^(\prime)=-(y)/(x-2y) \\ (dy)/(dx)=-(y)/(x-2y) \end{gathered}

User Ajiang
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.